Modelling K shell spectra from short pulse heated buried microdot targets - Hoarty,DJ; Sircombe,N; Beiersdorfer,P; Brown,CRD; Hill,MP; Hobbs,LMR; James,SF; Morton,J; Hill,E; Jeffery,M; Harris,JWO; Shepherd,R; et al. (High Energy Density Physics, 2017)
K shell X-ray emission measurements have been used to diagnose plasma conditions in short-pulse heated buried microdot targets on the Orion high power laser. These experiments have been used to validate simulations of short pulse laser-solid interaction that combine hybrid PIC modelling of the laser absorption with radiation-hydrodynamics simulations including an electron transport model. Comparison of these simulations with streaked K shell spectroscopy show the importance of including radial gradients in fitting the spectra. An example is presented of the emission of sulphur from a 50 µm diameter microdot sample buried in a plastic foil. Previously agreement between simulation and experiment was obtained only by treating the absorbed energy, electron temperature and beam divergence as fitting parameters. The good agreement obtained in this work used the measured laser energy and laser pulse length and calculated the laser-solid target interaction from first principles.